Program Induksi dan Supervisi Untuk Meningkatkan Kompentensi Guru Kota Salatiga - Laksono, Kabul; Nisa, Fakhrun; Rofi’ah, Nur; Hariyadi, Rahmat (El-Idare, 2023)
This study aims to get an in-depth description of the induction and supervision program expected by teachers at Salatiga City Vocational Schools. This study used a survey approach and the instrument used was a questionnaire. The research was conducted in several public and private SMKs in Salatiga City. The results of the study are that most teachers expect an induction and supervision program for novice teachers because the program has not been implemented evenly and sustainably in several educational institutions. The induction and supervision program carried out includes planning, implementation, and evaluation.